Multi-center evaluation of baseline neutrophil-to-lymphocyte (NLR) ratio as an independent predictor of mortality and clinical risk stratifier in idiopathic pulmonary fibrosis. (January 2023) - Mikolasch, Theresia A.; George, Peter M.; Sahota, Jagdeep; Nancarrow, Thomas; Barratt, Shaney L.; Woodhead, Felix A.; Kouranos, Vasilis; Cope, Victoria S.A.; Creamer, Andrew W.; Fidan, Silan; Ganeshan, Balaji; Hoy, Luke; et al.
Summary: Background: Idiopathic pulmonary fibrosis (IPF) is a progressive, fatal disorder with a variable disease trajectory. The aim of this study was to assess the potential of neutrophil-to-lymphocyte ratio (NLR) to predict outcomes in IPF. Methods: We adopted a two-stage discovery (n = 71) and validation (n = 134) design using patients from the UCL partners (UCLp) cohort. We then combined discovery and validation cohorts and included an additional 794 people with IPF, using real-life data from 5 other UK centers, to give a combined cohort of 999 patients. Data were collected from patients presenting over a 13-year period (2006–2019) with mean follow up of 3.7 years (censoring: 2018–2020). Findings: In the discovery analysis, we showed that high values of NLR (>/ = 2.9 vs < 2.9) were associated with increased risk of mortality in IPF (HR 2.04, 95% CI 1.09–3.81, n = 71, p = 0.025). This was confirmed in the validation (HR 1.91, 95% CI 1.15–3.18, n = 134, p = 0.0114) and combined cohorts (HR 1.65, n = 999, 95% CI 1.39–1.95; p < 0·0001). NLR correlated with GAP stage and GAP index (p < 0.0001). Stratifying patients by NLR category (low/high) showed significant differences in survival for GAP stage 2 (p < 0.0001), however not for GAP stage 1 or 3. In a multivariate analysis, a high NLR was an independent predictor of mortality/progression after adjustment for individual GAP components and steroid/anti-fibrotic use (p < 0·03). Furthermore, incorporation of baseline NLR in a modified GAP-stage/index, GAP–index/stage-plus, refined prognostic ability as measured by concordance (C)-index. Interpretation: We have identified NLR as a widely available test that significantly correlates with lung function, can predict outcomes in IPF and refines cohort staging with GAP. NLR may allow timely prioritisation of at-risk patients, even in the absence of lung function. Funding: Breathing Matters, GSK, CF Trust, BLF-Asthma, MRC, NIHR Alpha-1 Foundation .